Предмет: Алгебра,
автор: Аноним
1.4, 1.5 Срочно! Помогите
Приложения:
Ответы
Автор ответа:
0
1.4
y`=1/3*3cos²x*(-sinx)+sinx=sinx*(-cos²x+1)
y`(π/6)=sinπ/6*(-cos²π/6+1)=1/2*(-3/4+1)=1/2*1/4=1/8
1/5
f`(x)=4(x+1)/(x-1)*(x+1-x+1)/(x+1)²=4(x+1)/(x-1)*2/(x+1)²=8/[(x-1)(x+1)]=8/(x²-1)
f`(-3)=8/(9-1)=8/8=1
y`=1/3*3cos²x*(-sinx)+sinx=sinx*(-cos²x+1)
y`(π/6)=sinπ/6*(-cos²π/6+1)=1/2*(-3/4+1)=1/2*1/4=1/8
1/5
f`(x)=4(x+1)/(x-1)*(x+1-x+1)/(x+1)²=4(x+1)/(x-1)*2/(x+1)²=8/[(x-1)(x+1)]=8/(x²-1)
f`(-3)=8/(9-1)=8/8=1
Похожие вопросы
Предмет: Русский язык,
автор: abdusadikovtimur15
Предмет: Геометрия,
автор: Kolliad
Предмет: Алгебра,
автор: Аноним
Предмет: История,
автор: kustova19847236